2014
DOI: 10.1039/c3sc52072b
|View full text |Cite
|
Sign up to set email alerts
|

Switchable π-coordination and C–H metallation in small-cavity macrocyclic uranium and thorium complexes

Abstract: Actinide complexes of a small-cavity, dipyrrolide macrocycle exhibit unusual bent metallocene-type binding, or bis(arene)-type binding, or both at once in a di-uranium adduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
80
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 68 publications
9
80
0
1
Order By: Relevance
“…This O-C bond cleavage is common for reduced electropositive metal complexes, and supports the assignment of a reactive Np II centre in 3a. We have previously observed the double metalation of L Ar from the treatment of Th IV (L Ar ) complexes with either reductants or non-nucleophilic bases 16 , but the only occasion on which we have observed a An 3+ cation to reside in the cavity provided by the two pyrrolides (rather than the two arenes) is in the di-U III adduct, U III 2 I 4 (L Ar ) 16 . In this latter case, the 180 ligand undergoes a significant strain-energy penalty from the incorporation of two metal cations.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…This O-C bond cleavage is common for reduced electropositive metal complexes, and supports the assignment of a reactive Np II centre in 3a. We have previously observed the double metalation of L Ar from the treatment of Th IV (L Ar ) complexes with either reductants or non-nucleophilic bases 16 , but the only occasion on which we have observed a An 3+ cation to reside in the cavity provided by the two pyrrolides (rather than the two arenes) is in the di-U III adduct, U III 2 I 4 (L Ar ) 16 . In this latter case, the 180 ligand undergoes a significant strain-energy penalty from the incorporation of two metal cations.…”
Section: Resultsmentioning
confidence: 95%
“…Small, black plate-shaped crystals of 3a isolated from these solutions gave only weak diffraction. bound in the 'metallocene-type' geometry provided by the two η 5 -bound pyrrolide groups 16 . A dimer is formed through asymmetric methoxide bridging which has presumably arisen from the cleavage of dme.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 An alternative and very successful strategy has been the use of a single trianionic ligand framework to stabilize and coordinatively saturate the U(III) center while leaving a reactive pocket at the metal, with which to bind small molecules. 3 The latter complex makes use of stabilizing, π-symmetry bonding interactions 5 between the individual U(III) centers and either the two arenes (A, Chart 1) or the two pyrrolide (B, Chart 1) 6π-electron centers in the dinucleating macrocycle, and is an extremely rare example of a complex with two different U(III) coordination environments in the same compound. The degree of covalency in U-L bonding in both [U(L)I] and [U 2 I 4 (L)] was calculated, it was found that there was more covalent character to the U-pyrrolide bonding than to the U-arene bonding.…”
mentioning
confidence: 99%